Birds have primate-like numbers of neurons in the forebrain - Olkowicz, Seweryn; Kocourek, Martin; Lučan, Radek K; Porteš, Michal; Fitch, W Tecumseh; Herculano-Houzel, Suzana; Němec, Pavel (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Some birds achieve primate-like levels of cognition, even though their brains tend to be much smaller in absolute size. This poses a fundamental problem in comparative and computational neuroscience, because small brains are expected to have a lower information-processing capacity. Using the isotropic fractionator to determine numbers of neurons in specific brain regions, here we show that the brains of parrots and songbirds contain on average twice as many neurons as primate brains of the same mass, indicating that avian brains have higher neuron packing densities than mammalian brains. Additionally, corvids and parrots have much higher proportions of brain neurons located in the pallial telencephalon compared with primates or other mammals and birds. Thus, large-brained parrots and corvids have forebrain neuron counts equal to or greater than primates with much larger brains. We suggest that the large numbers of neurons concentrated in high densities in the telencephalon substantially contribute to the neural basis of avian intelligence.
Keywords: ptáci; počet buněk; Animals; Cell Count; Primates; mozek; Birds; Female; Neurons; zvířata; mužské pohlaví; primáti; Male; Brain; neurony; ženské pohlaví